2022
DOI: 10.1590/1806-9282.20220430
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication practices with conventional and herbal drugs among ear, nose, and throat patients

Abstract: OBJECTIVE: This study evaluates the self-practices with conventional and herbal drug use among ear, nose, and throat outpatients. METHODS: A cross-sectional survey-based study was carried out among all ear, nose, and throat outpatients on their first visit to the otorhinolaryngology department at a tertiary care hospital. The survey comprised a total of 14 questions with 4 different sections, including demographic characteristics, self-medication of conventional medicines, herbal medication usage, and percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Furthermore, smartphones are pivotal in telemedicine applications, facilitating tasks such as hearing loss screening and voice analysis. Three-dimensional printing technology is revolutionizing personalized patient care by enabling the fabrication of intraoperative implants, surgical guides, and anatomical models for training purposes [ 39 ]. This innovative technology enhances surgical precision and contributes to residency training in procedures such as peritonsillar abscess drainage and mastoidectomy [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, smartphones are pivotal in telemedicine applications, facilitating tasks such as hearing loss screening and voice analysis. Three-dimensional printing technology is revolutionizing personalized patient care by enabling the fabrication of intraoperative implants, surgical guides, and anatomical models for training purposes [ 39 ]. This innovative technology enhances surgical precision and contributes to residency training in procedures such as peritonsillar abscess drainage and mastoidectomy [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…Three-dimensional printing technology is revolutionizing personalized patient care by enabling the fabrication of intraoperative implants, surgical guides, and anatomical models for training purposes [ 39 ]. This innovative technology enhances surgical precision and contributes to residency training in procedures such as peritonsillar abscess drainage and mastoidectomy [ 39 ]. Emerging technologies and potential future diagnostics are shown in Figure 2 .…”
Section: Reviewmentioning
confidence: 99%
“…There are thousands of known herbs consist of various bioactive compounds [27][28][29][30]. But if we were to test for example 5,000 herbs and only make combinations of 2, then we have 12,497,500 combinations.…”
Section: Data Curation and Computational Analysis To Find The Effecti...mentioning
confidence: 99%
“…Medicinal plant preparations offer a compelling opportunity, providing beneficial health effects, treating ailments, and boosting immunity through their potent antioxidant, antimicrobial, antiviral, anti-inflammatory, and antitumor properties. However, research has indicated that self-administration of herbal products can result in exceeding optimal doses, leading to severe complications [21][22][23][24][25][26]. Therefore, the highly effective herb product development that addresses these concerns by providing controlled intake and release of biomolecules, increasing bioavailability, and minimizing toxicity is paramount.…”
Section: Introductionmentioning
confidence: 99%